Dekonstruksi Makna dan Bahasa dalam Perspektif Jacques Derrida - ., Natasha Constantin; ., Fitzerald Kennedy Sitorus (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Advertisement prevalence in society has been increasing throughout its growth. The field of advertising is always evolving in society, with settings and characteristics that are continually advancing. Advertisements has a formidable capacity to captivate individuals by using compelling language in suitable written content. In this scenario, advertising no longer serves as a supplementary component, but rather has evolved into a crucial aspect. The interpretation that arises in individuals' brains about a document or commercial often transforms into a collective and universally comprehended meaning. Deconstruction is a method that involves dissecting established meaning into smaller components, analyzing them, and reconstructing a new meaning that deviates from the commonly accepted understanding. Deconstruction fundamentally reconfigures established meanings into novel interpretations that may be seen as identical, like, or divergent significations. This article examines the principles of deconstruction from the viewpoint of Derrida. Through the adoption and use of advertising and deconstruction, one may get fresh perspectives on the significance and utility of deconstruction in the selection of language and text for commercials.